Theory of Limits Limits: Analysis of Limiting the Restriction of Fundamental Rights in the Brazilian Law - Clovis Demarchi; Fernanda Sell de Souto Goulart Fernandes (Revista Brasileira de Direitos e Garantias Fundamentais, 2015)
The article focuses on analyzing the application of the theory of limits of bounds by Brazilian courts. Thus, it was specified to analyze the control of the limitations and restrictions on the contents of fundamental rights in order maximize the Democratic State of Law purposes. To achieve such an approach, the research was divided into three stages: the first, there was an analysis of the fundamental rights and their relationship with the State and the Constitution; the second studied the possibility of restriction of fundamental rights; by the third, the limitation imposed analyzed the legislator and the law of the applicator on the restriction of fundamental rights by the theory of limits of bounds. Therefore it is considered that in the current phase of the Constitutional State, which emphasizes the normative force of the Constitution and the importance of fundamental rights, it is essential to get to the same effectiveness by achieving the constitutionally recognized rights. In this context, despite the possibility of relativity and restriction of fundamental rights, these not can be emptied so as not to be met by applying so the Theory of Limits Limits. The method used for the development of this study was inductive.